Temperature change and male infertility prevalence: an ecological study - Jiahua Qian; Chunbao Mo; Yuhe Si; Qianqian Zhang; Yihao Chen; Jiayu Zhu; Yifei Wang; Jianxiong Ma (BMC Public Health)
Abstract Background Although the effects of climate change on human health are widely recognized, its potential role in male infertility prevalence has not been thoroughly examined. This study seeks to explore the association between changes in ambient temperature and the prevalence of male infertility. Methods This ecological study encompassed 174 countries and regions. We utilized data from 2000 to 2019 on the age-standardized prevalence rate (ASPR) of male infertility and ambient temperature to assess their potential association. The analysis accounted for several covariates, including the Sociodemographic Index (SDI), continent, smoking prevalence, alcohol consumption per capita (APC), nitrogen dioxide (NO₂), and ozone (O₃). Annual temperature values were derived by averaging monthly temperatures, and the deviance percentage of temperature (DPT) was computed based on the 20-year mean temperature. To examine spatial and nonlinear relationships between temperature and male infertility ASPR, we applied the geographic detector approach and Restricted Cubic Spline (RCS) curves. Furthermore, linear mixed-effects models were employed to quantify the association between DPT and male infertility ASPR, and adjusted models were subsequently used to forecast changes in ASPR under projected temperature scenarios for 2020–2030. Results From 2000 to 2019, a spatial association was identified between temperature and the ASPR of male infertility. Additionally, a U-shaped correlation emerged, indicating the lowest ASPR at 15.7 °C. Higher DPT were linked to elevated male infertility ASPR, with an adjusted β estimate of 38.770 (95% CI: 8.392, 69.162). Projections suggest that ongoing temperature increases may continue to drive up male infertility ASPR. Conclusion Temperature change may be associated with an increased male infertility prevalence.